Philosophy 167: Class 14 - Part 9 - Further Revisions to De Motu: Select Definitions in De Motu Corporum in Mediis Regulariter Cedentibus. - Smith, George E. (George Edwin), 1938- (Tufts Archival Research Center, 2015)
Synopsis: Summarizes the changes in yet another version of De Motu.; Opening line: "This is a document, if it's a fragment. He's changed the title again on the motion of bodies in regularly yielding media."; Duration: 13:33 minutes.; Segment: Class 14, Part 9.